Features develop software for the design of concrete composition - Сизова, Наталья Дмитриевна; Михеев, Иван Андреевич (Eastern-European Journal of Enterprise Technologies, 2013)
The methods for solving the problem of concrete composition design of various research schools of materials science inUkraine:Rovno,Odessa,Kharkovschools are considered. The feasibility of application of information technologies for the formalization of various methods of concrete composition design is noted. The logical structure of intelligence decision-support system, which includes the information blocks and functional relations between them, is given. The functional requirements to the software, solving such problems were stated. These are simple interface, reasonable requirements to the hardware, reliability and safety, efficiency, user support. The fulfillment of the requirements is justified from the point of view of the possibility of software operation in the laboratory industrial conditions for the solution of the research and production tasks. The software user interface is given, primary and secondary problems are defined, which are solved using the information system